2009
DOI: 10.1007/s00702-009-0282-1
|View full text |Cite
|
Sign up to set email alerts
|

Far field potentials from brain stem after transcutaneous Vagus nerve stimulation: optimization of stimulation and recording parameters

Abstract: The method of vagus somatosensory evoked potentials (VSEP) was introduced to easily measure the activity of vagus brain stem nuclei. In Alzheimer's disease, this measure was characterized by longer latencies as compared to controls while amplitudes did not show statistical significant differences at frontal and central recording sites. Therefore, the influence of stimulation and recording parameters on amplitudes of VSEP were systematically examined. In 20 healthy participants, VSEP measurement was done by ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 19 publications
5
56
0
Order By: Relevance
“…The available evidence suggests that VN-SEP represents far field potentials of brainstem activity from vagus nuclei that can be elicited upon electrical stimulation of its auricular branch [8]. The present study disclosed significantly longer latencies in PD patients compared to controls, which may point to disease-related dysfunction of the sensory part of the vagus nerve (as part of the nucleus N. spinalis n. trigemini).…”
Section: Dear Sirssupporting
confidence: 46%
“…The available evidence suggests that VN-SEP represents far field potentials of brainstem activity from vagus nuclei that can be elicited upon electrical stimulation of its auricular branch [8]. The present study disclosed significantly longer latencies in PD patients compared to controls, which may point to disease-related dysfunction of the sensory part of the vagus nerve (as part of the nucleus N. spinalis n. trigemini).…”
Section: Dear Sirssupporting
confidence: 46%
“…Functional neuroimaging and neurochemical studies have also shown that tVNS on the afferent branch of vagus nerve can activate multiple brain areas involved in social and emotional regulation (Manta et al, 2009; Polak et al, 2009; Frangos et al, 2015). These activation patterns evoked by tVNS are similar to brain activity changes evoked by traditional VNS (Chae et al, 2003; Kraus et al, 2013; Frangos et al, 2015; Fang et al, 2016).…”
Section: Tvns Can Modulate the Brain Network Associated With The Neurmentioning
confidence: 99%
“…It has been suggested that stimulation of the dermatome corresponding to the auricular branch of the vagus nerve (Arnold’s nerve) in the external ear may be a non-invasive alternative to cVNS (Fig. 1) [58]. This is the region where the familiar “ear-cough reflex” can be elicited upon cutaneous stimulation and the dermatome is quite similar between rats and humans [9,10].…”
Section: Introductionmentioning
confidence: 99%